Implementasi Perencanaan Berbasis Data Untuk Meningkatkan Kesuksesan SPMB Sekolah Dasar - Fitriyani, Evi; Zulaikah, Ana; Prestianingsih, Eka; Nurdiyati, Nurdiyati; Nyoman, Ngurah Ayu (Universitas Sarjanawiyata Tamansiswa, 2025)
One indicator of the success of a school's marketing strategy is their ability to acquire new students according to target. Data-Based Planning (DBP) offers more mature planning for the success of PPDB. This study aims to describe the implementation of DBP in improving the success of SPMB at SD Negeri Potrobangsan 3 Kota Magelang and SD Negeri 2 Gondangwayang Temanggung. This study uses a qualitative approach. Data collection techniques use interviews, observations, and documentation . The validity of the data used is triangulation of techniques and data sources. Data processing is based on the Milles and Hubberman method. The results of the study show that a data-based approach to new student admissions helps improve the effectiveness of school strategies. Data helps schools can make more appropriate policies, follow enrollment trends, and consider various factors that affect the number of students. Data analysis helps schools understand opportunities and challenges, so that planning does not only focus on enrollment targets, but also on overall school development. During implementation, strategies designed based on data can be optimized. After that, an evaluation is important to ensure the strategy remains effective and to determine what data needs to be collected in the future.